Plasma vitamin K concentrations depend on CYP4F2 polymorphism and influence on anticoagulation in Japanese patients with warfarin therapy. Issue 5 (May 2015) - Hirai, Keita; Yamada, Yuto; Hayashi, Hideki; Tanaka, Masaki; Izumiya, Kohei; Suzuki, Masayuki; Yoshizawa, Misa; Moriwaki, Hideaki; Akimoto, Takehide; Tsuji, Daiki; Inoue, Kazuyuki; Itoh, Kunihiko
Abstract Introduction Warfarin is characterized by a large inter-individual variability in dosage requirement. This study aimed to analyze the contribution of the CYP4F2 genetic polymorphism and plasma vitamin K concentration on the warfarin pharmacodynamics in patients and to clarify the plasma vitamin K concentration affecting warfarin sensitivity index in rats. Materials and Methods Genetic analyses of selected genes were performed and plasma concentrations of warfarin, vitamin K1 (VK1) and menaquinone-4 (MK-4) were measured in 217 Japanese patients. We also assessed the association of plasma VK1 and MK-4 concentrations with the warfarin sensitivity index (INR/Cp) in rats. Results Patients with the CYP4F2 (rs2108622) TT genotype had significantly higher plasma VK1 and MK-4 concentrations than those with CC and CT genotypes. The multiple linear regression model including VKORC1, CYP4F2, and CYP2C9 genetic variants, age, and weight could explain 42% of the variability in warfarin dosage. The contribution of CYP4F2 polymorphism was estimated to be 2.2%. In contrast, plasma VK1 and MK-4 concentrations were not significantly associated with warfarin dosage in patients. Nevertheless, we were able to demonstrate that the warfarin sensitivity index was attenuated and negatively correlated with plasma VK1 concentration by the oral administration of VK1 in rats, as it resulted in a higher VK1 concentration than that in patients. Conclusions The plasma VK1 and MK-4 concentrations are significantly influenced by CYP4F2 genetic polymorphism but not associated with warfarin therapy at the observed concentration in Japanese patients. The CYP4F2 polymorphism is poorly associated with inter-individual variability of warfarin dosage requirement.